The Effect of Using Retelling Story Towards Students’ Speaking Ability at Islamic Senior High School - Sukrida, Alifa Yuning; Safitri, Loli; Kardena, Absharini; Sakti, Genta (STIT Ahlussunnah Bukittinggi, 2025)
The research conducted this research because researcher found several problems in the process of learning English. Those problems were related with learning English and also related through observation in the class at Islamic Senior High School 1 Pasaman. The first is the teacher still used teacher centered teaching. The second is many of the students has limited vocabulary. The third is most of students get difficulties to express their idea. The last is some of the students that is unable to speak English Fluently. In this case, this research was going to find out whether there was a significant effect of Retelling Story on students’ speaking ability in the eleventh grade of Islamic Senior High School 1 Pasaman. This research used quantitative research with quasi-experimental research as the design by using pre-test and post-test for acquiring the research data. The subject of this research were two classes were F.2 (XI IAI) as experiment class and F.3 (XI IPA) control class that consist of 61 students. The data was gotten from the students’ speaking test that were given before and after the treatment. After calculating the data, it was found that the mean score of pretest in experimental class was 50.00 and the post test was 90.00. it means that Retelling Story had a significant effect on students’ speaking ability in eleventh grade of Islamic Senior High School 1 Pasaman.